The Transition Mechanism of The Limited Access Order - The Emergence And Evolution of Institutions In Kenya - Jobo, Sisamkele (School of Economics, 2019)
The purpose of this dissertation was to study the institutional transmission mechanism of the limited-access social order in Kenya. This was motivated by the theory of new institutional economics, which views differences in institutions as fundamental in explaining differences in the level of economic development across countries. However, this theory often faces criticism in as far as it provides weak or no evidence pertaining to the direction of causality between institutions and economic development. This is because the theory tends to neglect the problems of political instability and the process state formation. In the social order framework, the problems of violence and instability underpin state formation and consequently institutional development. The limited access theory suggests that openness to the political and economic spheres of influence at early stages of development serves to increase instability and the level of violence in a society, and this may lead to a deteriorating quality of institutions, hence further economic stagnation. Using the theoretical framework of social orders and public choice theory a Vector Autoregressive Model was applied in order to evaluate this prediction of the limited access order theory. The results indicate that in inheriting colonial institutions and using them to bolster their elite networks through patronage, African leaders invariably inherited the contradictions embodying colonial rule, whereby open access to customary economic rights is disruptive to elite capital accumulation, thereby leading to political instability. Additionally, while the literature on postcolonial African states suggests that colonial institutions have been persistent, the results indicate that postcolonial Kenya has better institutions than colonial Kenya, in terms of economic and political rights. Moreover while the theory mainly attributes violence to elite competition, the findings highlight the importance the increase in political consciousness in the postcolonial state in explaining the evolution of institutions.